Apakah Perceived Ease Of Use, Perceived Usefulness, Perceived Trust, Dan Persepsi Risiko Berpengauh Terhadap Intention To Use E-Money Dengan Pendekatan Technology Acceptance Model (TAM)? - Biduri, Sarwenda; Hariyanto, Wiwit; Loekitasari, Silvy; Irma Suyani, Ade (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2021)
Abstract The purpose of this study was to determine the effect of Perceived ease of use, Perceived usefulness, Perceived trust, and Perceived risk partially on the intention to use e-money with the Technology Acceptance Model approach. This research method uses a quantitative approach. The data collection technique is a questionnaire. The samples were determined using convenience sampling. The total respondents in this study were 74 respondents. The data analysis technique used SPSS software. The results of the study prove that partially the variables Perceived ease of use, Perceived usefulness, and Perceived trust affect the intention to use e-money. Perception of risk has no effect on the intention to use e-money.